The Programmed Death-1 Pathway Counter-Regulates Inflammation-Induced Osteoclast Activity in Clinical and Experimental Settings - Greisen, Stinne R.; Kragstrup, Tue W.; Thomsen, Jesper Skovhus; Hørslev-Pedersen, Kim; Hetland, Merete Lund; Stengaard-Pedersen, Kristian; Østergaard, Mikkel; Ørnbjerg, Lykke; Junker, Peter; Sharpe, Arlene H.; Freeman, Gordon J.; Hvid, Malene; et al. (Frontiers in Immunology, 2022)
Objective The programmed death-1 (PD-1) pathway is essential for maintaining self-tolerance and plays an important role in autoimmunity, including rheumatoid arthritis (RA). Here, we investigated how membrane-bound and soluble (s)PD-1 influence bone homeostasis during chronic inflammation, exemplified in RA. Methods Bone mineral density and bone microstructure were examined in PD-1 and PD-L1 knockout (KO) mice and compared with wild-type (WT) mice. Receptor activator of nuclear factor kappa-B ligand (RANKL) was measured in serum, and the expression examined on activated bone marrow cells. Osteoclast formation was examined in cells from murine spleen and bone marrow and from human synovial fluid cells. sPD-1 was measured in chronic and early (e)RA patients and correlated to markers of disease activity and radiographic scores. Results PD-1 and PD-L1 KO mice showed signs of osteoporosis. This was supported by a significantly reduced trabecular bone volume fraction and deteriorated microstructure, as well as increased osteoclast formation and an increased RANKL/OPG ratio. The recombinant form of sPD-1 decreased osteoclast formation in vitro, but was closely associated with disease activity markers in eRA patients. Sustained elevated sPD-1 levels indicated ongoing inflammation and were associated with increased radiographic progression. Conclusion The PD-1 pathway is closely associated with bone homeostasis, and lacking members of this pathway causes a deteriorated bone structure. The immunological balance in the microenvironment determines how the PD-1 pathway regulates osteoclast formation. In eRA patients, sPD-1 may serve as a biomarker, reflecting residual but clinically silent disease activity and radiographic progression.